Value of Spring Fertilization of Bahiagrass - Rob Kalmbacher; Mark Wade (EDIS)
This is EDIS document FE348, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published March 2003.